IMPLEMENTASI PENGARUSUTAMAAN GENDER (PUG) SEBAGAI STRATEGI PENCAPAIAN KESETARAAN GENDER (STUDI DI PROVINSI SUMATERA UTARA DAN JAWA TENGAH) - Martiany, Dina (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2011)
Implementation of Gender Mainstreaming is a strategy to achieve Gender Equality, started with Gender Analysis. Its efectiveness as a strategy influenced by significant factors. This article aims to analyse how the implementation of Ministry of Internal Affairs Regulation Number 15 Year 2008 and the obstacles occurred in Province of Central of Java and North of Sumatera, also how to increase Gender Mainstreaming effectiveness and strictly reach the goals. The Method of data analysis applied a descriptive qualitative approach. Based on data collection conducted in both local areas, founded that Gender Mainstreaming is uncommitted coverage yet. Implementation of Ministry of Internal Affairs Regulation Number 15 Year 2008 about General Instruction of Implementation of Gender Mainstreaming in the Local Area should be improved. Therefore, regulation of gender mainstreaming urgently needed to formulated in a part of comprehensive act.